La femme allaitant des serpents et ses liens avec la Luxure - Raphaël Guesuraga (Bulletin du Centre d’Études Médiévales d’Auxerre)
Since the nineteenth century, it is a fact recognized by all that the woman suckling snakes in Romanesque sculpture is a representation of lust. However, several elements would tend to strongly put in perspective this affirmation. The few texts encountered on this motive come as much from the register of sexuality as that of motherhood. A serial study of the iconographic type also relativizes the sexual nature of this woman with snakes, who is not always naked, who almost never sex attacked. Conversely, an investigation of the representations of Lust as a capital sin throughout the Middle Ages shows that it is rather depicted as a woman looking in a mirror than by a woman suckling snakes. In these conditions, it would be less the generic representation of lust, than a category of women particularly stigmatized by the Romanesque patrons.